Antitumor Activity of a Duocarmycin Analogue Rationalized to Be Metabolically Activated by Cytochrome P450 1A1 in Human Transitional Cell Carcinoma of the Bladder - Sutherland, Mark; Gill, Jason H.; Loadman, Paul M.; Laye, Jonathan P.; Sheldrake, Helen M.; Illingworth, Nicola A.; Alandas, Mohammed N.; Cooper, Patricia A.; Searcey, Mark; Pors, Klaus; Shnyder, Steve D.; Patterson, Laurence H. (Molecular cancer therapeutics, 2013)
We identify cytochrome P450 1A1 (CYP1A1) as a target for tumor-selective drug development in bladder cancer and describe the characterization of ICT2700, designed to be metabolized from a prodrug to a potent cytotoxin selectively by CYP1A1. Elevated CYP1A1 expression was shown in human bladder cancer relative to normal human tissues. RT112 bladder cancer cells, endogenously expressing CYP1A1, were selectively chemosensitive to ICT2700, whereas EJ138 bladder cells that do not express CYP1A1 were significantly less responsive. Introduction of CYP1A1 into EJ138 cells resulted in 75-fold increased chemosensitivity to ICT2700 relative to wild-type EJ138. Negligible chemosensitivity was observed in ICT2700 in EJ138 cells expressing CYP1A2 or with exposure of EJ138 cells to CYP1B1- or CYP3A4-generated metabolites of ICT2700. Chemosensitivity to ICT2700 was also negated in EJ138-CYP1A1 cells by the CYP1 inhibitor α-naphthoflavone. Furthermore, ICT2700 did not induce expression of the AhR-regulated CYP1 family, indicating that constitutive CYP1A1 expression is sufficient for activation of ICT2700. Consistent with the selective activity by CYP1A1 was a time and concentration-dependent increase in γ-H2AX protein expression, indicative of DNA damage, associated with the activation of ICT2700 in RT112 but not EJ138 cells. In mice-bearing CYP1A1-positive and negative isogenic tumors, ICT2700 administration resulted in an antitumor response only in the CYP1A1-expressing tumor model. This antitumor response was associated with detection of the CYP1A1-activated metabolite in tumors but not in the liver. Our findings support the further development of ICT2700 as a tumor-selective treatment for human bladder cancers. Mol Cancer Ther; 12(1); 27–37. ©2012 AACR.